2009
DOI: 10.1093/cercor/bhp122
|View full text |Cite
|
Sign up to set email alerts
|

Altered Water Diffusivity in Cortical Association Tracts in Children with Early Deprivation Identified with Tract-Based Spatial Statistics (TBSS)

Abstract: Institutional rearing is associated with neurocognitive and behavioral difficulties. Although such difficulties are thought to reflect abnormal neurologic development resulting from early social deprivation (ED) and there is evidence for functional abnormality in children with histories of ED, the impact of early deprivation on brain anatomy has received little study in humans. The present study utilized an objective and sensitive neuroimaging analysis technique (Tract-Based Spatial Statistics) to evaluate whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
108
0
9

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(129 citation statements)
references
References 64 publications
12
108
0
9
Order By: Relevance
“…Existing evidence documents There is already substantial evidence of effects of institutionalization on neurodevelopment. Indeed, reports of brain anatomical and functional differences between family-and institutionally-reared children are accumulating rapidly (Behen et al, 2009;Chugani et al, 2001;Eluvathingal et al, 2006;Gee et al, 2013;Govindan, Behen, Helder, Makki, & Chugani, 2010;Hodel et al, 2015;Maheu et al, 2010;Mehta et al, 2009;Sheridan, Fox, Zeanah, McLaughlin, & Nelson, 2012;Tottenham et al, 2011;Tottenham et al, 2010).…”
Section: Neurodevelopmental Consequences Of Institutionalizationmentioning
confidence: 99%
“…Existing evidence documents There is already substantial evidence of effects of institutionalization on neurodevelopment. Indeed, reports of brain anatomical and functional differences between family-and institutionally-reared children are accumulating rapidly (Behen et al, 2009;Chugani et al, 2001;Eluvathingal et al, 2006;Gee et al, 2013;Govindan, Behen, Helder, Makki, & Chugani, 2010;Hodel et al, 2015;Maheu et al, 2010;Mehta et al, 2009;Sheridan, Fox, Zeanah, McLaughlin, & Nelson, 2012;Tottenham et al, 2011;Tottenham et al, 2010).…”
Section: Neurodevelopmental Consequences Of Institutionalizationmentioning
confidence: 99%
“…In addition, post institutionalized children present abnormities in some bundles that connect the different cortical areas. In this regard, several recent studies have reported a lower fractional anisotropy values in the left uncinate fasciculus and in the superior longitudinal fascicule in post institutionalized children compared to children without this personal background [12,13]. In a functional level, Chugani et al [14] reported a reduction in glucose metabolism in the amygdala and hippocampus during rest conditions in post institutionalized children compared to never institutionalized children and neurological patients.…”
Section: Institutionalization and Brain/cognitive Affectationmentioning
confidence: 95%
“…Therefore, the functional coupling between prefrontal and temporal areas could participate in the manipulation of socialemotional information and this coupling is in part performed by uncinate fasciculus which provides strong connections between those regions [52]. This bundle, in the left hemisphere, shows a lower density in the institutionalized population [12,13]. Related with the communication between areas, gamma band has been related with this function on other works [53].…”
Section: Eeg Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Des modifications de l'hippocampe sont également observées lors de stress intenses et prolongés Pinto et al, 2015;Polan & Hoffer, 2008). Au niveau cortical supérieur, soit les régions du cortex frontal, préfrontal et temporal, une activité métabolique limitée ainsi qu'un développement anormal de la substance blanche sont rapportés chez les enfants institutionnalisés ayant vécu de multiples formes de négligence Govindan, Behen, Helder, Makki, & Chugani, 2010). Sur le plan comportemental, un fonctionnement anormal des zones frontales du cerveau aura un effet majeur sur de nombreux processus régulant les comportements, les apprentissages, l'expression des émotions et les habiletés sociales puisque ces zones sont impliquées dans la modulation des capacités réflexives, la mémoire de travail , le contrôle de l'attention (Lavie & de Fockert, 2006), l'inhibition motrice, la réorientation et la mise à jour des comportements (Levy & Wagner, 2011), ainsi que dans l'expression de la sympathie, la gêne, la culpabilité et la compréhension et le respect des règles sociales (Anderson, Bechara, Damasio, Tranel, & Damasio, 1999 …”
Section: Les Mécanismes Du Stress Et La Réaction Face Aux Situations unclassified